1994
DOI: 10.1111/j.1469-8749.1994.tb11895.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity in Infants and Children With Down Syndrome

Abstract: SUMMARY The authors used the Teller acuity cards to assess the visual acuity of 51 infants and children with Down syndrome aged between two months and 18 years. The success rate and test times were comparable to those reported for normally developing children. Even those subjects in the study who were free of ocular disorders and/or who were wearing optical correction during testing showed significantly poorer visual acuity than individuals without Down syndrome. The development of visual acuity in infants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 25 publications
1
53
0
1
Order By: Relevance
“…33 Measurements of accommodation and subjective depth of field in individual amblyopic subjects support this model. 33 Decreased visual acuity is often present in individuals with DS 34 and could contribute to lower accommodative responses and increased lags, much as in amblyopes without DS. The average best corrected visual acuities in this study were 20/45 (range ϭ 20/25 to 20/100) and are in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…33 Measurements of accommodation and subjective depth of field in individual amblyopic subjects support this model. 33 Decreased visual acuity is often present in individuals with DS 34 and could contribute to lower accommodative responses and increased lags, much as in amblyopes without DS. The average best corrected visual acuities in this study were 20/45 (range ϭ 20/25 to 20/100) and are in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is common to find acuity values between 6/30 and 6/9 for DS children between the ages of 6 to 12 years. 24,25 It has recently been shown that this is not due to behavioral differences in test performance between children with and without DS-the differences remained when objective testing was used. 26 It is possible that the constant under-accommodation for distances closer than infinity might result in a subtle bilateral amblyopia.…”
mentioning
confidence: 94%
“…Individuals with DS also show alterations in sensory modalities. They typically achieve poorer results in tests of sensitivity [5] and visual acuity [6] and show sensorineural hearing loss that affects the inner ear [7]. In addition, DS individuals seem to have difficulty integrating sensory information from various modalities, becoming more dependent on the visual [8], although this issue is not fully understood [9].…”
Section: Introductionmentioning
confidence: 99%